PERAN PEREMPUAN SEPANJANG PERKEMBANGAN SEJARAH PERADABAN ISLAM - Agus Santri (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
Islam puts women in an honorable position, even one of the suras in the Qur'an is An-Nisa (4th surah in the Qur'an) which means "Woman". Its contents revolve around Shari'a laws related to women, such as verses about marriage, pologami, inheritance, husband and wife association and so on. The history of Islamic civilization is events or events that occurred in the past and have been perpetuated where at that time Islam was the main force and the cause of the emergence of a culture that has a system of technology, building art, fine art, state systems and advanced and complex science . So, Islam, Islamic teachings underlie the birth of civilization at that time. This is because Islam has spread widely in communities throughout the world. Examples of women who play a major role in Islamic civilization are the wives of the Prophet Muhammad and his daughters. In general, there are many names of Muslim women who give a big role to Islamic civilization, which contributes greatly to Islamic civilization.